Development and performance evaluation of a blancher cum dryer for jackfruit - Anupama B M (Department of Food and Agricultural process Engineering, Kelappaji College of Agricultural Engineering and Technology, 2017)
Jackfruit is an indigenous and underutilised tropical fruit rich in nutrients. It can be consumed as both fruit in the ripe and as vegetable in the unripe stage. Jackfruit is a seasonal crop as to ensure its year round availability, appropriate processing protocols are to be standardised to develop quality products. Dehydration is one of the most widely used preservative methods to increase the shelf life of the product. Steam blanching along with preservatives is essential step to accelerate the drying rate and to prevent quality deterioration. In the traditional jackfruit drying process protocol, separate drying and blanching were utilised which increased both the production and as well as occupied more plant space. In this scenario there is a great demand for the development of a blancher cum dryer for jackfruit. In the present study blancher cum dryer with a volume of 2.052 m3 and capacity was fabricated and evaluated at different loading rate. Blanching time of 7 min and preservatives (0.2% citric acid, 0.1% KMS and 0.5% turmeric powder) were standardised based on enzyme inactivation, texture and colour retention. Slices were dried in three different drying temperatures (60, 65 and 70°C) at various loadings (L1 (3.8), L2 (4.8) and L3 (5.8) kg/m2. Dehydrated slices were packed in LDPE 100 μm bags and kept for storage studies at ambient atmospheric condition for a period of ten months. Quality analysis viz., moisture content, water activity, TSS, pH, vitamin C, texture, colour and microbial analysis were carried out at every one month storage interval. At the end of storage period best quality and microbiologically safe samples were selected for the sensory evaluation. Based on the sensory qualities maximum overall score was obtained for L2T1 (loading capacity 23 kg at 60°C) combination and hence was selected. Developed machine was compared with the existing model in terms of loading capacity, power and time consumption, labour cost, fabrication cost and quality of the dehydrated samples. The overall cost for the development of blancher cum dryer was Rs.2,00,000/-. The total production cost of one kg dehydrated jackfruit slices in blancher cum dryer and existing model were Rs.172/- and 180/- respectively.